Melodies of cinema: the royal pre-Talkie film performances in Caracas, 1899-1930 - Sueiro Villanueva, Yolanda (2023)
Never was a film projected in absolute silence. Several musical acoustics were incorporated, at the beginning or in the middle of the screening —we ignore with what effective level of connection—, to the film show that was completely surrounded by noises from outside and inside the auditorium. At the same time, the projections made up of various films were inserted in variety programmes including ballets, comedy acts, attractions and others. The music would have the function —in Burch’s words— of combating the contamination of diegetic silence, caused by uncontrolled noises coming from outside, by the swaying of the audience in the hall, conversations, etc., replacing it with an organised sound space, a sort of «red thread stretched between the film and the spectator», in the words of Marcel L’Herbier. This work aims to initiate the practice, from the perspective of film history, of compiling the musicians and musical practices that took place in Venezuela during the years of silent cinema.